How-to Design and Implement Academic Program and Course Sharing Partnerships - Anderson, Dawn (My University, 2010)
The PowerPoint presentation “How-To Design and Implement Academic Program and Course Sharing Partnerships” was delivered as a session at the Midwest Consortium: Rural Health and Health Disparities Research in the Heartland during faculty and administrator track session 2 on June 10, 2010, at the University of Kansas Medical Center School of Nursing, Kansas City, Kansas. The 38 slides summarize how Kansas State University’s Institute for Academic Alliances develops and manages collaborative distance education. The presentation exemplifies three collaboration models, gives fast track ideas to implement course exchanges, and gives an overview of ExpanSIS, a secure, web-based student information system for multi-institution course and program management.
Keywords: Course sharing; Consortiums; ExpanSIS